Media Puzzle Bergambar Hewan Sebagai Strategi Kreatif untuk Meningkatkan Kemampuan Membaca Permulaan Anak Usia Dini - Siregar, Rafli Muharamsyah; Sit, Masganti (Journal of Practice Learning and Educational Development, 2025)
Emergent reading skills constitute a critical foundation in early childhood literacy development. This study aims to examine the impact of utilizing animal picture puzzle media on improving the emergent reading abilities of students at RA Islamiyah Batang Kuis. The research employed a two-cycle Classroom Action Research (CAR) design with a sample of 14 students from Class B. Data were collected through observation sheets using indicators such as pronouncing letter sounds, distinguishing letters, identifying words with the same initial letter, and articulating words clearly. Data analysis was conducted descriptively by calculating the percentage of development within each category. The findings revealed a significant improvement: the “Not Yet Developed” category decreased from 27% in Cycle I to 0% in Cycle II, while the categories “Developing as Expected” and “Highly Developed” increased. The most notable progress was observed in the ability to distinguish letters (an increase of 14%), followed by the ability to articulate words clearly. These findings are consistent with global evidence emphasizing the effectiveness of play-based learning in supporting early literacy and cognitive development in children. The implications of this study suggest that animal picture puzzles can serve as an alternative, creative, and enjoyable strategy in early childhood reading instruction. Nevertheless, the study is limited by its small sample size, single-class context, and short duration without a control group. Future research is recommended to involve a larger number of participants, extend the duration, and employ a more rigorous experimental design, including variations of other play-based media relevant to early literacy.